2021
DOI: 10.2147/jaa.s266999
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-Guided Asthma Therapy: An Alternative Approach to Guidelines

Abstract: Despite recent advances in therapy, a substantial proportion of asthmatics remain not well controlled. The classical stepwise approach to pharmacological therapy in adult asthma recommends that treatment is progressively stepped up by increasing the inhaled corticosteroid (ICS) dose or by adding another controller medication-to achieve symptom control and reduce the risk of exacerbations, and stepped down after a period of control. In general, asthma guideline recommendations do not reflect that there are sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The frequency of adverse events was low. Thus, in the era of personalized medicine and targeted therapy, phenotyping-based management of asthma may be an effective approach to optimize the management of patients with moderate to severe uncontrolled asthma [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of adverse events was low. Thus, in the era of personalized medicine and targeted therapy, phenotyping-based management of asthma may be an effective approach to optimize the management of patients with moderate to severe uncontrolled asthma [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Many factors should be considered during study design for efficient management of asthma. For example, they need to ensure that their findings have applicability for various settings and patient populations and that they have a patient-centred focus, such as that taken in pragmatic comparative effectiveness studies (de Llano et al, 2021). Nonetheless, although there is an ongoing need for further research in some areas, the evidence base in support of patient-centred and co-management approaches to asthma is strong (Ödling, 2021).…”
Section: Table (1): Assessing Asthma Severity (Nhlbi Guidelines 2020) Nhlbi: National Heart Lung and Blood Institutementioning
confidence: 99%
“… 5 Allergic asthma and asthma with high eosinophil counts are associated with type 2 (T2) inflammation, mediated by the cytokines interleukin (IL)-4, IL-5, and IL-13, as well as by immunoglobulin (Ig)E. These endotypes can account for up to approximately 80% of all patients with asthma. 6–8 The pathophysiology underlying the non-T2 asthma, or T2-low, endotype has not been fully elucidated, and may have biomarker elements that overlap with T2 asthma. Structural changes to the airways involving smooth muscle cell hypertrophy and neutrophil infiltration driven by IL-17 have been reported in the non-T2 endotype.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline blood eosinophil count, FeNO level, and serum specific IgE status are inflammatory biomarkers used by clinicians to inform treatment decisions. 6 Biomarker assessment can be useful for defining asthma molecular phenotypes, as well as for predicting disease course or response to therapy. In the tezepelumab development program subgroup analyses of patients in clinical trials defined by baseline inflammatory biomarker status demonstrated that tezepelumab treatment responses were comparable across subgroups.…”
Section: Introductionmentioning
confidence: 99%